Special Spot Day Care Graduation in Watkins' Backyard - Watkins, Howard::::::::: (1983)
Cathy Wille, Jim Kratzer, Nancy Bleile-Kratzer holding Annie Bleile-Kratzer, Annie Tilley, Greg Wille holding Maya Wille; back row: Eva, David Tilley Jake Tilley, Robin Watkins in baby swing, Christine Watkins, ? Sitting on backyard lawn